Two dimension of motion of the inverted pendulum using a belting system / Irma Harianie Djuli Muhd Nur Djuly and Zaimah Daud - Muhd Nur Djuly, Irma Harianie Djuli; Daud, Zaimah (1994)
Inverted pendulum is a classical problem in control theory. It has been used many times as a model on how to control an unstabilize system. Many control theorists and engineers had studied this problem using different controlling methods and construction of the model. The main objective is to stabilize the unstable state of the inverted pendulum, i.e. to maintain the inverted pendulum vertically. The approach for this thesis win be based on a two dimension of motion using a pulley-belt transmission system. The main thrust of this project is on the construction of the plant and modelling of the system. The importance of studying this system is that, it enables us to relate to the real system, such as the study of monopod walking machine and biped locomotive machine and the representation of a dynamic model of a space booster on take off.